Draft Genome Sequence of Staphylococcus aureus ST672, an Emerging Disease Clone from India - Khedkar, Supriya (American Society for Microbiology, 2012)
We report the draft genome sequence of methicillin-resistant Staphylococcus aureus (MRSA) strain ST672, an emerging disease clone in India, from a septicemia patient. The genome size is about 2.82 Mb with 2,485 open reading frames (ORFs). The staphylococcal cassette chromosome mec (SCCmec) element (type V) and immune evasion cluster appear to be different from those of strain ST772 on preliminary examination.